A STUDY ON WOMEN ENTREPRENEURSHIP IN KANYAKUMARI DISTRICT - S. Vasheela Banu; C. Benjamin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The increasing presence of women as entrepreneurs has led to significant business and economic growth in the country. Women-owned business enterprises are playing a prominent role in society by generating employment opportunities in the country, bringing in demographic shifts and inspiring the next generation of women founders. With a vision to promote the sustainable development of women entrepreneurs for balanced growth in the country, Startup India is committed towards strengthening women entrepreneurship in India through initiatives, schemes, creation of enabling networks and communities and activating partnerships among diverse stakeholders in the startup ecosystem.